UETS/EFR World Wide Net: a new network paradigm, simple, secure, highly scalable and energy-efficient. (6th December 2010) - Barroso, Jose Morales
The Universal Ethernet Telecommunications Service (UETS) is a highly scalable, high performance and energy efficient Layer 2 network architecture, protocols and addressing schema with greatly improved security, bandwidth and efficiency. This technology will be a practical, effective and innovative solution for the interconnection network, through a combination of electronic and optical technologies, to deliver the future high capacity switches required for applications and support the massive amount of traffic related to quadruple-play services of the Future Internet, reducing, at the same time, the aggregate energy consumption by several orders of magnitude.